CASE REPORT: REACTIVATION OF CONGENITAL OCULAR TOXOPLASMOSIS IN AN IMMUNOCOMPETENT PATIENT AFTER RECEIVING MEASLES - Markovska, Vesna Celeva; Pandilov, Stefan; Jovanov, Zoran (Journal of Morphological Sciences, 2022)
A case of recurrent ocular toxoplasmosis, presented through diagnostic imaging techniques and laboratory tests. To show the course and development of the clinical picture of ocular toxoplasmosis in a 19-year-old girl with good visual acuity in both eyes, which was accidentally detected during a routine ophthalmological examination for a driver's license. At the University Clinic for Eye Diseases in Skopje, several imaging diagnostic methods have been performed, such as: fundus photography, aurofluorescence, optical coherence tomography (OCT) and fundus fluorescence angiography (FFA). Imaging techniques, along with laboratory tests for specific anti-toxoplasmosis IgG and IgM antibodies, have helped to diagnose this not-so-common entity-ocular toxoplasmosis. The development of the disease was followed by a clinical picture, certain diagnostic methods in a period of seven years. Three recurrences of the parasitosis occurred during that period. The third attack of toxoplasmosis was associated with the occurrence of measles in an otherwise healthy young woman, a possible trigger for reactivation of the disease. Regular laboratory tests of anti-toxoplasma IgG and IgM antibody titers were performed with the help of ELISA at PHI UC for infectious diseases and febrile conditions in Skopje, during the entire process of monitoring. The lesion described by the diagnostic modalities corresponded to the data obtained from the literature and together with the elevated values ​​of anti-toxoplasma IgG and IgM antibodies confirmed the diagnosis of congenital ocular toxoplasmosis. Keywords: toxoplasmosis, ocular toxoplasmosis, therapy, laboratory tests, FFA, OCT